Agrribisnis Pergudangan Benih Bawang Merah (Studi Kasus di Kelompok Tani Sarimakmur) - Agus Surata; Indah Widowati (Jurnal Dinamika Sosial Ekonomi, 2001)
The purpose of this research was to detect the value and revenue, the cost, the profit accounting rate of return, payback period, dan net present value, the "SARIMAKMUR, Kreek, district of Bantul, in 2001. The data was collected by interviewing the management staff, and being analyzed by accounting and cash flow method, and tabel. The result indicated that the revenue Rp 84.000.000, the cost Rp 45.190.333,33, the profit us Rp 38.909.667,67, the NPV a Rp140.050.000,- and the project feableKeywords the value and revenue, rate of return, project feasible